SEBUAH ANALISIS: INFLASI, TINGKAT PENGANGGURAN DAN PERTUMBUHAN EKONOMI DI JAWA TIMUR PERIODE 2022 - Zahida I’tisoma Billah (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2024)
The problem of unemployment is a problem that is very difficult to avoid and can be avoided by a country or region, causing social problems such as crime and economic problems. This condition can reduce people's welfare and purchasing power. The lower the country's unemployment rate, the richer people live and vice versa. To overcome the problem of unemployment, attention is needed not only from a micro point of view, but also from a macro point of view. Macro policy is very important. One of the things to watch out for is inflation and economic growth. This research aims to determine the influence of the inflation rate and unemployment rate on economic growth in East Java, and to determine the variables that most dominantly influence economic growth in East Java. This study examines the influence of inflation and economic growth on unemployment in East Java. The data used in this research includes secondary data from the Finnish Central Bureau of Statistics (BPS) and browsing. Online site as support. The analytical method used in this research is multiple linear regression analysis. Keyword:Inflation, Unemployment, and Economic Growth.